The Analysis of Public Policies for the Strengthening of Cultural and Creative Industries: a Documentary-Bibliometric Review of the Literature - Gómez-Reyes, Flor Marleny; Catalá-Pérez, Daniel; de-Miguel-Molina, María (Revista del CLAD Reforma y Democracia, 2023)
This article conducts a systematic review of the literature on public policies in cultural and creative industries, with the aim of identifying its evolution, schools of thought and new research trends in this field. The methodology used is the content and bibliometric analysis of literature, supported by analysis tools such as Scopus, WoS, Excel, VOSviewer, Tree of Science and RStudio Cloud. The conjoint analysis graphs were performed with Github. The results show that the literature referring to the object of study formally began in the 1990s, strengthening at the beginning of the 21st century and evolving its concepts around its impact on the development of the countries. This evolution can be classified into four main thematic clusters: 1) focused on research into innovation and knowledge, 2) creative economy, 3) development of cities and 4) cultural economy. Cluster 1 is shown more dispersed in the graph, product of the article exploration, thus showing the new trend that marks the changes of the economic processes in the countries, new authors and directing the attention towards “knowledge” and “innovation” that is woven around the systems of public policies, economy, companies and the incidence of the synergies of these concepts in the economic, urban and regional development. As a main contribution, this research provides a bibliometric basis and support to academics and policy makers in cultural and creative industries on why new research should focus on cluster 1, aimed at the fifth industrial revolution and the changes brought to this field by the COVID-19 pandemic.
Keywords: Public Policy; Cultural Policy; Cultural Industry; OECD Countries; Analytical Bibliography